Energy consumption, environmental degradation, economic growth and financial development in globe: Dynamic simultaneous equations panel analysis - Sher Khan; Zhuangzhuang Peng; Yongdong Liu (Energy Reports, 2019)
We use a panel data set of 193 countries over 1990-2017 period, by employ the Seemingly unrelated regression (SUR), three stage least squares regression (3SLS), dynamic model two-step generalized method of moments and two-step system generalized method of moments approach to investigate the impacts of financial development, economic growth, energy consumption, and carbon emission on each other. The empirical results suggested that financial development, economic growth, energy consumption, and carbon emissions are affected one another but with high pollution spread, except for consumption of energy which decreases financial development. All models confirm the Environmental Kuznets Curve for the global panel. The implications of all results for carbon emissions, financial development, economic growth, and energy policy are discussed.
Keywords: 330; CO2 emissions; Dynamic model two-step GMM and System GMM; Economic growth; Energy consumption; Financial development; Seemingly unrelated regressions (SUR)